Synthesis and Evaluation of a Series of 3, 4, 5‐Trimethoxycinnamic Acid Derivatives as Potential Antinarcotic Agents. (26th December 2012) - Jung, Jae‐Chul; Moon, Sohyeon; Min, Dongguk; Park, Woo Kyu; Jung, Mankil; Oh, Seikwan
<x xml:space="preserve">Abstract</x> A series of 3, 4, 5‐trimethoxycinnamic acid derivatives was prepared and evaluated for antinarcotic effects on morphine dependence in mice and binding affinities on serotonergic receptors. The key synthetic strategies involve generation of ketones 6–7, esters 9–12 through condensation reaction, and amides 13–19 via coupling reaction using 1‐hydroxybenzotriazole/ethyl(dimethylaminopropryl)carbodiimide system in high yield. We found that the naloxone‐induced morphine withdrawal syndrome was significantly suppressed by new synthetic 3, 4, 5‐trimethoxycinnamic acid derivatives (20 mg/kg/day). Most of 3, 4, 5‐trimethoxycinnamic acid derivatives were found to have high affinity to 5‐HT1A receptor. The naloxone‐induced morphine withdrawal syndrome was attenuated by (+)8‐OH‐DPAT (0.1 mg/kg/day, i.p.), a 5‐HT1A receptor agonist. In cortical neuronal cells, (+)8‐OH‐DPAT (1 μm) produced an elevation of the pERK 1/2 expression, and the elevated pERK levels were inhibited by WAY 100635, a 5‐HT1A receptor‐specific antagonist. Interestingly, the pERK levels were increased by the 3, 4, 5‐trimethoxycinnamic acid derivatives and the derivatives‐mediated changes in pERK levels were blocked by the WAY 100635. These results suggested that new synthetic 3, 4, 5‐trimethoxycinnamic acid derivatives have a potential antinarcotic effect through acting as a 5‐HT1A receptor agonist in mice.